Improving Students' Digital Literacy and Higher-Order Thinking Skills Through the Development of Flipbook Media for Physics Learning - Septina Severina Lumbantobing; Andreas Rian Nugroho (Journal of Natural Science and Integration, 2026)
This study aims to develop a feasible and effective flipbook learning medium to improve digital literacy and students' higher-order thinking skills (HOTS) in Physics learning. The study was conducted at SMA Negeri 1 Jonggol, with a sample of 32 students, and was determined using a purposive sampling technique. The research method for module development uses the Research and Development (R&D) type, with the ADDIE development model, which comprises five stages: analysis, design, development, implementation, and evaluation. To improve HOTS using a quasi-experimental method. The research design used a one–group pretest–posttest design. The research instruments include a questionnaire to assess the feasibility of flipbook media, a digital literacy questionnaire, and test questions to measure students' HOTS abilities. The results of the study show that the developed flipbook media is in the very good category, based on student assessments (89.94%) and teacher assessments (86.6%). Students perceived the developed media as engaging due to its integration of images, audio, and video, which facilitates interactive and contextual learning experiences. The improvement in students’ digital literacy was categorized as good, with a 80% score, indicating that the flipbook media is effective in enhancing digital literacy across the technical, cognitive, and socio-ethical dimensions. Furthermore, the N-gain score for improving Higher Order Thinking Skills (HOTS) was 0.62, which falls within the moderate category. These findings suggest that flipbook media is an effective instructional innovation for promoting both students’ digital literacy and HOTS. Keywords: flipbook, HOTS, digital literacy, learning